Valorization of rice stubble through biodegradation using hydrolytic enzyme-producing Olivibacter oleidegradans CMB10 and Agrobacterium pusense SFMB9 - Milind Gajbhiye; Sushmita Patil; Sagar Awate; Supriya Kokare; Siddharth Terdale; Manish Kumar Dubey (Heliyon)
Hydrolytic enzymes (cellulase, pectinase, xylanase) producing bacteria were isolated from compost, garden soil and wastewater. Out of 63 bacterial isolates, CMB10 and SFMB9, were selected for study due to their enzymatic potential, with relative enzyme activity ranging from 0.5 to 0.8. Both were Gram-negative, rod-shaped and non-motile. They were phenotypically characterized concerning Bergey's Manual of Determinative Bacteriology followed by molecular characterization by 16S rRNA gene sequencing and CMB10 and SFMB9 were identified as Olivibacter oleidegradans and Agrobacterium pusense, respectively. The two isolates were tested in-vitro for rice stubble degradation. The highest stubble degradation (86.3 %) was recorded in the case of co-inoculated treatment on 45th day as compared with individual microbial treatments (P < 0.05). However, there was a significant difference between all the bacterial treatments and uninoculated control on 15, 30 and 45th day of incubation. Scanning electron microscopic images confirm the distortion of microfibrillar structure of stubble by cultures. The activity of all hydrolytic enzymes was detected on all the days post-inocualtion, where, cellulase activity was at the highest (95.77 U/ml). There was an effective decrease in C/N ratio in all inoculated trials from 26.4 to 14.2 in 45 days of composting. This compost had a positive stimulatory effect on the growth of Glycin max, evidenced by ≈ 10 % increase in chlorophyll content of leaves, and ≈25–45 % increase in root and shoot length, respectively, as compared to uninoculated control. The isolates reported here for the first time concerning rice stubble degradation, show potential for large-scale stubble degradation.